IMPLEMENTASI TEMPLATE WEB RESPONSIVE DYNAMIS (STUDI KASUS: WEBSITE LEMBAGA PENJAMINAN MUTU DAN PENGEMBANGAN PENDIDIKAN) - Gunawan Gunawan; Sandhy Fernandes (Program Studi Sistem Informasi, Universitas Banten Jaya, 2021)
LPMPP function as an institution that is fully responsible for the implementation of quality assurance mechanisms that have been established based PPEPP Internal Quality Assurance System (SPMI) as determined by UM Bengkulu. In fact, LPMPP has yet to have an information system website that provides all the information needed for applications for re-accreditation of tertiary institutions and study programs. The provision of the website is expected to provide information about the activities that have been implemented by LPMPP with responsive displays that adapts to the screen size of the mobile phone. Website supported by the dynamic capabilities that can provide system data information is up to date.